2023
DOI: 10.1149/2162-8777/acbedc
|View full text |Cite
|
Sign up to set email alerts
|

Structure-Performance Relationships of Complexing Agents on the Chemical Mechanical Polishing of 6063 Aluminum Alloy

Abstract: Aluminum alloy has wide applications in many industries due to its unique properties. Chemical mechanical polishing (CMP) is commonly used to treat aluminum alloy to generate mirror-finish surface. In this study, the effects of pH and H2O2 concentration on the CMP of 6063 aluminum alloy were studied. Better CMP performance was obtained in basic media with 1.0 wt% H2O2. Moreover, complexing agents with different structures and functional groups were evaluated for the CMP of Al-alloy, and their structure-perform… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 43 publications
(72 reference statements)
0
0
0
Order By: Relevance
“…Sun et al 8 investigated the effect of the complexing agent glycine in a polishing slurry at pH 7.5 on the MRR of the aluminum alloy CMP, and found that glycine and TAZ synergistically formed a weak passive layer on the surface of Al, which protected the surface of Al from the effects of chemical dissolution as well as achieved a high polishing rate. Li et al 9 investigated the effect of complexing agents with different structures and functional groups on the MRR and surface roughness Ra of the aluminum alloy CMP, and found that complexing power, steric hindrance, and electrostatic repulsion of complexing agents were the important factors in determining the MRR and surface roughness Ra. In summary, the pH, H 2 O 2 concentration, and complexing agents of the polishing slurry play an important role in the MRR and surface roughness Ra of the alloy CMP.…”
mentioning
confidence: 99%
“…Sun et al 8 investigated the effect of the complexing agent glycine in a polishing slurry at pH 7.5 on the MRR of the aluminum alloy CMP, and found that glycine and TAZ synergistically formed a weak passive layer on the surface of Al, which protected the surface of Al from the effects of chemical dissolution as well as achieved a high polishing rate. Li et al 9 investigated the effect of complexing agents with different structures and functional groups on the MRR and surface roughness Ra of the aluminum alloy CMP, and found that complexing power, steric hindrance, and electrostatic repulsion of complexing agents were the important factors in determining the MRR and surface roughness Ra. In summary, the pH, H 2 O 2 concentration, and complexing agents of the polishing slurry play an important role in the MRR and surface roughness Ra of the alloy CMP.…”
mentioning
confidence: 99%